Ecoprint Techniques as An Environmentally Friendly Fashion Product - Kristanti, Kristanti; Laila Ramadhani, Noor; Pandansari, Purwosiwi (Yayasan Meira Visi Persada, 2024)
The textile industry is one of the contributors to the highest amount of waste in the world. One of the wastes produced by the textile industry is liquid waste which comes from the remains of synthetic dyes which contain several dangerous chemicals. An alternative that can be done to reduce liquid waste from synthetic dyes is to switch to using natural dyes that come from plants. One technique that can be used to color textiles is the ecoprint technique. The ecoprint technique is a process for transferring color and shape to fabric through direct contact. The ecoprint technique uses materials from plant parts that contain color pigments such as leaves, flowers, bark, etc. Products produced from ecoprints can be a business opportunity because ecoprints have artistic value and high selling value. The research method used is literature study by taking reference sources in the form of international journals and national journals. The purpose of writing this article is to describe ecoprint as a business opportunity that can be generated by fashion.